Examining The Harmonization of Gen Z Workers in Implementing Optimal Employee Performance Based on Emotion Focus Coping - I Kadek Arya Wibawa Saputra; Gine Das Prena (Yayasan Riset dan Pengembangan Intelektual, 2023)
Generation Z is known as individuals who are creative at work, but are also prone to high stress and anxiety related to high job demands. This research aims to identify the emotional influence on Generation Z's performance in the workplace and to formulate emotion-based coping strategies to minimize the negative impact of these emotions and increase optimal performance. Data collection methods used include observation, in-depth interviews, and documentation. This research aims to explore the impact of implementing Emotion Focused Coping in creating harmonization and optimal performance in the workplace for Generation Z. The results of this research are expected to provide valuable insights and provide appropriate recommendations for practitioners and researchers in the field of human resource management.